(untitled) (Research, Society and Development, 2021)
Domestic violence is any act or omission that causes death, injury, physical, sexual or psychological suffering, and moral or property damage. The dental surgeon is one of the professionals who has greater contact with these victims, due to the greater involvement in the orofacial region of the abused patients. The objective of the present study is to discuss the importance of the academic training of dental surgeons in the face of domestic violence. The research was carried out with students of the dentistry course of a university of Natal/RN, of the ninth period. For data collection and validation, questionnaires were applied individually and reserved for each one. 57 students participated in the study. They stated that the dental surgeon should know and be responsible for identifying and diagnosing cases of domestic violence, 54 (94.7%) of the interviewees. As for the measures that should be taken, by the professional, the choice to "notify the aggression" was the most reported. In relation to the subject being addressed in the course, 30 (52.6%) students reported having had contact with the subject studied, of these, most of the interviewees 16 (53.3%), answered not to remember when this happened. With this research, it was concluded that there is a need for a greater approach on this subject by the teachers who teach the basic disciplines of the curriculum grid, because, although the participants responded positively to the questions, an insecurity and deficiency in relation to the proposed theme has been noted.